International Variations in Perceptions of Accounting Journals - Nobes, Christopher W. (The Accounting Review, 1985)
[The study on perceptions of quality of accounting journals by Howard and Nikolai [1983] is extended to include respondents from the U.K., Australia, and New Zealand. There are highly significant correlations between the perceptions of faculty in these three countries. There is also a high correlation with the earlier U.S. study, though the ranking of a few journals is markedly different.]